2023
DOI: 10.1523/eneuro.0471-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Network Inhibition in the Dentate Gyrus of Adult Neuroligin-4 Knock-Out Mice

Abstract: Loss-of-function mutations in neuroligin-4 (Nlgn4), a member of the neuroligin family of postsynaptic adhesion proteins, cause autism spectrum disorder in humans. Nlgn4 knockout (KO) in mice leads to social behavior deficits and complex alterations of synaptic inhibition or excitation, depending on the brain region. In the present work, we comprehensively analyzed synaptic function and plasticity at the cellular and network levels in hippocampal dentate gyrus of Nlgn4 KO mice. Compared with wild-type littermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A prior study has shown that the loss of Nlgn4 caused postsynaptic changes at inhibitory synapses and aberrant inhibitory neurotransmission, heavily disrupting γ-oscillations in the CA3 region of the mouse hippocampus ( 176 ). Unexpectedly, Muellerleile and colleagues discovered increased network inhibition within the dentate gyrus of adult Nlgn4 KO mice but unaltered in neonatal Nlgn4 KO mice ( 177 ). Guneykaya et al.…”
Section: Abnormalities In the Structure And Function Of The Hippocamp...mentioning
confidence: 99%
“…A prior study has shown that the loss of Nlgn4 caused postsynaptic changes at inhibitory synapses and aberrant inhibitory neurotransmission, heavily disrupting γ-oscillations in the CA3 region of the mouse hippocampus ( 176 ). Unexpectedly, Muellerleile and colleagues discovered increased network inhibition within the dentate gyrus of adult Nlgn4 KO mice but unaltered in neonatal Nlgn4 KO mice ( 177 ). Guneykaya et al.…”
Section: Abnormalities In the Structure And Function Of The Hippocamp...mentioning
confidence: 99%